2023
DOI: 10.2166/wcc.2023.401
|View full text |Cite
|
Sign up to set email alerts
|

Energy efficiency and water use indices for sweet potato (Ipomoea batatas L.) production under subtropical climatic conditions of Bangladesh

Abstract: For estimation of energy use efficiency for sweet potato production in the riverbank areas of Bangladesh under subtropical climatic conditions, a study was conducted with sweet potato producers of the respective areas from 60 individuals (12 producers' for each sweet potato variety) by using a structural questionnaire. The results revealed that the majority of the energy input was consumed by the pre-harvest activities (22,313.55 MJ ha−1 or 90.85%), of which fertilizer application (36.84%) and irrigation (35.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Sweet potato generally needs adequate water during the growing cycle [ 45 ]. Management of water supply has an impact on optimal sweet potato yields [ 46 ]. In this study, all three environments had sufficient average rainfall for the growth of sweet potatoes ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Sweet potato generally needs adequate water during the growing cycle [ 45 ]. Management of water supply has an impact on optimal sweet potato yields [ 46 ]. In this study, all three environments had sufficient average rainfall for the growth of sweet potatoes ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Epp-h = Herbicide energy input, GJ/ha Epp-p = Pesticide energy input, GJ/ha Total herbicide input, GJ/ha =Her × Heqv (10) Where, Her = Applied rate (kg or lit/ha) of herbicide Heqv = Energy equivalent (GJ/kg or lit) of herbicide Total pesticide input, GJ/ha = Pes × Peqv (11) Where, Pes = Application rate (kg or lit/ha) of pesticide Peqv = Energy equivalent (GJ/kg or lit) of pesticide Irrigation energy input, GJ/ha = Iw × Ieqv (…”
Section: Total Energy Inputmentioning
confidence: 99%
“…Effective energy use in agriculture is one of the conditions for sustainable agricultural production which provides financial savings [8]. Many researchers have studied energy and economic analysis to determine the energy efficiency of crop production, such maize [9], rice [8], potato [10], sweet potato [11]. However, no studies have been published on the energy and economic analysis of potato production in Bangladesh.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, Mbayaki and Kinama (2022) reported the water use efficiency and water productivity of two sweet potato varieties in Kenia, and the values are 39.8, 30 kg ha −1 mm −1 , and 1.11, 0.95 kg m −3 , respectively. Alam et al (2023) reported the water‐energy productivity of sweet potato in Bangladesh as 1.32 g m −3 MJ −1 with an average water productivity of 4.97 kg m −3 and average water use efficiency of 28.33. Thus, water productivity and water use efficiency may change for crop variety and location (Dladla et al, 2018).…”
Section: Resilience Of Sweet Potato To Environmental Variables‐abioti...mentioning
confidence: 99%